Proceedings of the 6th International Conference on Web Intelligence, Mining and Semantics 2016
DOI: 10.1145/2912845.2912852
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid recommendation system for news in a mobile environment

Abstract: Over the last few years consumption of news articles has shifted more and more from the written versions towards the web. Mobile devices, which became more powerful, with larger screens and connected to the Internet, have had a great influence on this paradigm change. A critical problem associated to online news is related to the fact that the large number of daily articles can be overwhelming to the users. Recommendation services can largely improve the efficiency and accuracy of acquired information. These s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…They assumed that user experience is a global phenomenon for all users, so they use one measure for all. For some researchers, it can be measured through accuracy (Nguyen et al 2014;Viana and Soares 2016;Su et al 2016). They demonstrated that higher ratings provide more pleasing and satisfactory experience to the users.…”
Section: Subjective Measures Through User Study On User Satisfactionmentioning
confidence: 99%
“…They assumed that user experience is a global phenomenon for all users, so they use one measure for all. For some researchers, it can be measured through accuracy (Nguyen et al 2014;Viana and Soares 2016;Su et al 2016). They demonstrated that higher ratings provide more pleasing and satisfactory experience to the users.…”
Section: Subjective Measures Through User Study On User Satisfactionmentioning
confidence: 99%
“…Both, present a slight increase of publications since 2016 that demonstrates to more advanced methods (Babanejad et al, 2020;Hazrati & Elahi, 2021). Approaches that use temporal features (Muralidhar et al, 2015), movie and mobile solutions (Tewari et al, 2016;Viana & Soares, 2016), collaborative filtering applications (Saranya & Sadasivam, 2017;Wang et al, 2017) or neural networks to solve the cold-start problem (Misztal- In what automated journalism concerns, the most part of the articles focus on exploratory studies (RQ1). Approaches focus on understanding ethical issues and the impact on the working practices of journalists in digital newsrooms (Carlson, 2014;García-Avilés, 2014), on the potentialities and pitfalls for news organizations (S. C. , as well as analyze the user perception to automated news (Zheng et al, 2018).…”
Section: (Rq3)mentioning
confidence: 99%
“…Methodologies considering user location [21], mobile devices [22][23][24], or social networks [19], have also emerged because of the dissemination of these devices and applications among the population. Besides the academic community proposals, several adaptive commercial news recommending systems, such as Google News and Yahoo!…”
Section: News Personalizationmentioning
confidence: 99%